Doña Mencía: un centro receptor de la terra sigillata hispánica de Los Villares de Andújar (Jáen, España) - Fernández-García, M.ª Isabel; Moreno-Alcaide, Manuel (Rei Cretariae Romanae Fautorum Acta, 2022)
This article aims to understand the diffusion of terra sigillata produced in the pottery workshop of Isturgi (Los Villares de Andújar, Jaén) based on the study of the ceramics deposited in the Historical-Archaeological Museum of Doña Mencía (Córdova). This observation brings us closer to a more diversified commercial geography than we originally supposed. The ceramics documented in these places are limited to the first two generations of Isturgitan potters.